Oxidation of Pear Seed Oil During Storage - Otache, Abel; Obi, Amaebino; Chinelo, Stella; Ejeomo, Christopher; Bobby, Enakireru Davis; Ufuoma, Esemedafe Josephine (Journal of Science and Technology, 2022)
The effects of storage on the oxidative deterioration of crude Pear Seeds Oil (PSO), obtained by soxhlet extraction, were studied. Oxidation was monitored after 6 months via several analytical techniques: peroxide value, iodine value, free fatty acids, Fourier-transform infrared spectroscopy (FTIR), and Gas chromatography–mass spectrometry (GC-MS). The slow detorioration of the oil was an indication that oxidation was strongly dependent on temperature, oxygen availability and the presence of Cu2+. The mass spectra from the GC-MS results reveal the formation of secondary oxidation products, thereby denoting a transformation of primary hydroxyperoxides. This assertion is further strengthen based on the increasing value of the total Saturated Fatty Acids (SFA) from 26.09 to 29.44 % and a corresponding decrease for Unsaturated Fatty Acid (UFA) from 71.28 to 68.80 %. Other physicochemical analysis, shows that an average Iodine value recorded a reduction from 40.377 to 39.193 at a rate of 2.9 %, free fatty acid also recorded an increase at 15.18 %. Furthermore, the acid value also recorded a 2.60 % reduction. An increase in the peroxide value from 6.243 to 7.452 at a rate of 16.22 %, is a confirmation of possible formation of secondary oxidation products as revealed by the GC-MS mass spectra. Therefore the need to pay close attention during production, transportation as well as the presence of possible Cu2+ is key to addressing slow oxidation that is capable of impairing the quality of the oil.